Book Review: Business Model for Economic Development of Pesantren based on Renewable Energy - Rahayu, Solihah Sari (SMART Insight, 2025)
This article presents an analytical summary of the book Business Model for Economic Development of Islamic Boarding Schools Based on Renewable Energy published by the Department of Sharia Economics and Finance of Bank Indonesia (2022). The book offers a conceptual and practical framework for the economic development of Islamic boarding schools through the use of renewable energy, especially Solar Power Plants (PLTS), in the context of energy transition and sustainable development. By integrating the economic perspective of Islamic boarding schools, national energy policies, and Islamic normative foundations through the Maqashid Syariah approach, this book places pesantren as strategic actors in mainstreaming green and low-carbon economies. This article summarizes the main ideas of the book, including the historical and social role of Islamic boarding schools, the urgency of the energy transition, technical aspects of solar PV, business models of renewable energy-based Islamic boarding schools, as well as future opportunities and challenges. This summary is expected to be an academic reference for researchers, policymakers, and practitioners in the sustainable and inclusive economic development of Islamic boarding schools.